UNIMAS 3rd International Nursing Students’ Conference 2025 on 24th May 2025 - Dev Nath, Kaushal (UNIMAS Gazette, 2025)
Universiti Malaysia Sarawak (UNIMAS) is pleased to announce that the Faculty of Medicine and Health Sciences will be organizing the UNIMAS 3rd International Nursing Students’ Conference (INSC) at Dewan Tunku Abdul Rahman Putra (DeTAR Putra), UNIMAS, Kota Samarahan on the 24th May 2025.